Pathways Exploring the Routes of a Movement Heritage - Svensson, Daniel; Saltzman, Katarina; Sörlin, Sverker (The White Horse Press, 2022)
This anthology explores possibilities to acknowledge human motion, and traces thereof, as heritage. Today, with the increasing interest in local and sustainable connections, and in bodily and spiritual enhancement, we see a growing use of walking tracks both in landscapes within reach from urban centres and in more remotely located or 'wild' areas. The corona pandemic has further propelled these trends. Of course, landscapes that are commonly understood as wilderness or 'nature' are in most cases clearly influenced by human actions and movements. While walking trails tend to be regarded as pathways to experience nature and as tools to promote public health, they could also be seen and used as routes to culture and history, indeed as pathways to the past. Based on a Swedish research project with the aim to explore the multiple dimensions of walking, paths and movement, this volume engages and discusses the potential effects of such an expansion of the heritage register.